2020
DOI: 10.1155/2020/1409376
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Menopause‐Associated Hepatic Lipid Metabolic Disorders by Herbal Formula HPC03 on Ovariectomized Rats

Abstract: Postmenopausal women have an increased risk of developing nonalcoholic fatty liver disease (NAFLD). We formulated a combination of three herb mixtures (HPC03) and observed lipid-lowering efficacy. HepG2 cells were treated with oleic acid to induce an NAFLD model (in vitro). Also, we investigated potential of HPC03 in an ovariectomize- (OVX-) induced NAFLD model (in vivo). We separated the mice into six groups, as follows: SHAM, OVX, OVX + β-estradiol, and OVX + HPC03 (50, 100, and 200 mg/kg). Rats were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Although AST is mainly present in the cytoplasm of hepatocytes, AST is found in the cytoplasm and mitochondria of the heart, liver, and kidneys. We accordingly assessed the effects of pumpkin seed extract in the different rat groups by determining the levels of these hepatic markers of liver function, with the results indicating that menopause can influence the levels of AST and ALT, and treatment with pumpkin seed extract can rectify the abnormal levels of these enzymes; the normal range of AST and ALT has been reported in a previous study [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although AST is mainly present in the cytoplasm of hepatocytes, AST is found in the cytoplasm and mitochondria of the heart, liver, and kidneys. We accordingly assessed the effects of pumpkin seed extract in the different rat groups by determining the levels of these hepatic markers of liver function, with the results indicating that menopause can influence the levels of AST and ALT, and treatment with pumpkin seed extract can rectify the abnormal levels of these enzymes; the normal range of AST and ALT has been reported in a previous study [43].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Trembling et al and Sumida et al confirmed that long-term estrogen deficiency may increase the risk of NAFLD fibrosis in postmenopausal women (Sumida et al, 2020;Trembling et al, 2020). Similarly, the ovariectomized (OVX) rodent models suggest a causal relationship between estrogen deficiency and increased susceptibility to NAFLD (Li et al, 2013;Jeong et al, 2018;Chang et al, 2020). Estrogen deficiency plays an important role in NAFLD pathogenesis in postmenopausal women.…”
Section: Introductionmentioning
confidence: 98%